ANALISIS PENGARUH RASIO KINERJA KEUANGAN TERHADAP HARGA SAHAM PT BANK MANDIRI PERSERO PERIODE 2014 – 2019 - WIJAYA, I KETUT KUSUMA (GANEC SWARA, 2021)
Share prices occur according to market supply and demand. Demand for shares is influenced by investors' expectations of the issuing company. The better the financial performance of a company, the higher investor expectations will be. This results in the shares becoming increasingly attractive and the share price will be higher. Conversely, if a company's financial performance is not good, investors' expectations will be low, so investors are not interested in investing in these shares. This causes the stock price to fall. The company's financial performance can be done by analyzing financial reports. This study aims to determine the effect of financial performance ratios on stock prices. The analytical tool used is multiple linear regression and hypothesis testing is done by partial test (T-test) and simultaneous test (F-test) and standardized coefficient test.     Based on the research results that simultaneously the financial ratio variable does not have a significant effect on stock prices. Meanwhile, only partially the NPM variable affects stock prices. Meanwhile, the financial performance variables (CAR, ROA, and LDR) do not affect stock prices. For the adjusted R2 value of 99.80%, it means that this value means that the variation of the independent variable which can explain the dependent variable is 99.80% and the remaining 2% is the variation of other variables that are not explained in the model.